DIMORFISME SEKSUAL DALAM KARAKTERISTIK EPIGENETIS UPPER VISCEROCRANIUM DARI SAMPEL TENGKORAK MANUSIA GILIMANUK (BALI) - Rusyad Adi Suriyanto (BRIN, 2006)
The practical relevance of this research is that it enables us to be able to recognize or distinguish male and female upper viscerocrani by qualitative methods, especially from paleoanthropological and archaeological human remains which are more commonly found in fractured, brittle and poorly preserved conditions. Research on the Gilimanuk skull sample shows that the epigenetic characteristics of the palatinal foramen size (depth), the degree of expression of the palatine torus, the degree of expression of the maxillary torus, the strength of the tubercular marginale projection and the size (depth) of the zygomaticofasiale foramen can help determine the sex of the individual, regardless of racial factors, changes. age and environment.